The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1292/jvms.001609
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokines Suppress the Expression Level of Protease-Activated Receptor-2 through the Induction of iNOS in Rat Colon

Abstract: ABSTRACT. Protease-activated receptor (PAR)-2 plays important roles in intestinal inflammatory responses and also contributes to intestinal digestive motility. In the distal colon of a rat experimental colitis model, expression level of PAR-2 mRNA was decreased, and relaxation through PAR-2 activation was attenuated. This study shows the effects of proinflammatory cytokines on changes to PAR-2 in rat colonic smooth muscle using an organ culture method. Colonic inflammation was induced in rats by administering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In an in-vitro assay of mouse stomach and guinea pig taenia coli, activation of PAR1 and PAR2 by their respective synthetic agonists, resulted in relaxation of the gastric fundus 22 . Other studies have reported varied results that have been dependent on the inflammatory conditions of the model and focused on www.nature.com/scientificreports/ other segments of the GI tract such as the jejunum or colon, which support a GI-segment specific, differential response to inflammation in GI function [23][24][25] . Another possible pathway by which zonulin affects GI motility is by the modulation of the innate immune system and its downstream interaction with neuro-enteric components of the GI tract 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In an in-vitro assay of mouse stomach and guinea pig taenia coli, activation of PAR1 and PAR2 by their respective synthetic agonists, resulted in relaxation of the gastric fundus 22 . Other studies have reported varied results that have been dependent on the inflammatory conditions of the model and focused on www.nature.com/scientificreports/ other segments of the GI tract such as the jejunum or colon, which support a GI-segment specific, differential response to inflammation in GI function [23][24][25] . Another possible pathway by which zonulin affects GI motility is by the modulation of the innate immune system and its downstream interaction with neuro-enteric components of the GI tract 26 .…”
Section: Discussionmentioning
confidence: 99%